ANALISIS LITERATUR IMPLEMENTASI WEB-BASED KNOWLEDGE MANAGEMENT SYSTEM DALAM MANAJEMEN BENCANA DI INDONESIA - Wardhana, Arya Wijaya Pramodha; Sugihartati, Rahma; Laksmi, Laksmi; Irawati, Indira (Jurnal Abdi Insani, 2024)
Disaster management in Indonesia faces complex challenges due to the high risks of various natural disasters. In this context, a web-based knowledge management system (KMS) has been identified as a potential solution to enhance the effectiveness and efficiency of information management during emergencies. This research presents a systematic literature review aiming to evaluate the implementation of web-based KMS in disaster management in Indonesia. Through careful analysis of several related studies and reports, this research identifies trends, challenges, and best practices in the implementation of web-based KMS. The analysis results indicate that web-based KMS has significant potential for facilitating real-time information collection, storage, and distribution, which are crucial in disaster emergency situations. However, challenges such as uneven technological infrastructure, a lack of trained human resources, and inadequate policy support hinder effective implementation. Proposed strategic recommendations include strengthening technological infrastructure, providing continuous training for KMS users, and enhancing cross-sector collaboration. Strong policy support from the government is also deemed essential to encourage widespread adoption and use of KMS.